Functional and genetic analyses of ZYG11B provide evidences for its involvement in OAVS. Issue 10 (1st August 2020) - Tingaud‐Sequeira, Angèle; Trimouille, Aurélien; Marlin, Sandrine; Lopez, Estelle; Berenguer, Marie; Gherbi, Souad; Arveiler, Benoit; Lacombe, Didier; Rooryck, Caroline
Abstract: Background: The Oculo‐Auriculo‐Vertebral Spectrum (OAVS) or Goldenhar Syndrome is an embryonic developmental disorder characterized by hemifacial microsomia associated with auricular, ocular and vertebral malformations. The clinical heterogeneity of this spectrum and its incomplete penetrance limited the molecular diagnosis. In this study, we describe a novel causative gene, ZYG11B . Methods: A sporadic case of OAVS was analyzed by whole exome sequencing in trio strategy. The identified candidate gene, ZYG11B, was screened in 143 patients by next generation sequencing. Overexpression and immunofluorescence of wild‐type and mutated ZYG11B forms were performed in Hela cells. Moreover, morpholinos were used for transient knockdown of its homologue in zebrafish embryo. Results: A nonsense de novo heterozygous variant in ZYG11B, (NM_024646, c.1609G>T, p.Glu537*) was identified in a single OAVS patient. This variant leads in vitro to a truncated protein whose subcellular localization is altered. Transient knockdown of the zebrafish homologue gene confirmed its role in craniofacial cartilages architecture and in notochord development. Moreover, ZYG11B expression regulates a cartilage master regulator, SOX6, and is regulated by Retinoic Acid, a known developmental toxic molecule leading to clinical features of OAVS. Conclusion: Based on genetic, cellular and animal model data, we proposed ZYG11B as a novel rare causative gene for OAVS. Abstract : The Oculo‐Auriculo‐Vertebral Spectrum or Goldenhar Syndrome is an embryonic developmental disorder characterized by hemifacial microsomia associated with auricular, ocular and vertebral malformations. Its etiology is poorly characterized. In this study, we describe a novel causative gene, ZYG11B.